Ancient Terracottas from South Italy and Sicily in the J. Paul Getty Museum - Maria Lucia Ferruzza (Getty Publications, 2016)
In the ancient world, terracotta sculpture was ubiquitous. Readily available and economicalunlike stone suitable for carvingclay allowed artisans to craft figures of remarkable variety and expressiveness. Terracottas from South Italy and Sicily attest to the prolific coroplastic workshops that supplied sacred and decorative images for sanctuaries, settlements, and cemeteries. Sixty terracottas are investigated here by noted scholar Maria Lucia Ferruzza, comprising a selection of significant types from the Getty